Phylogenetic Analysis and Molecular Dating Suggest That Hemidactylus anamallensis Is Not a Member of the Hemidactylus Radiation and Has an Ancient Late Cretaceous Origin - Bansal, Rohini; Karanth, K. Praveen (PLOS ONE, 2013)
Background of the Work The phylogenetic position and evolution of Hemidactylus anamallensis (family Gekkonidae) has been much debated in recent times. In the past it has been variously assigned to genus Hoplodactylus (Diplodactylidae) as well as a monotypic genus ‘Dravidogecko’ (Gekkonidae). Since 1995, this species has been assigned to Hemidactylus, but there is much disagreement between authors regarding its phylogenetic position within this genus. In a recent molecular study H. anamallensis was sister to Hemidactylus but appeared distinct from it in both mitochondrial and nuclear markers. However, this study did not include genera closely allied to Hemidactylus, thus a robust evaluation of this hypothesis was not undertaken. Methods The objective of this study was to investigate the phylogenetic position of H. anamallensis within the gekkonid radiation. To this end, several nuclear and mitochondrial markers were sequenced from H. anamallensis, selected members of the Hemidactylus radiation and genera closely allied to Hemidactylus. These sequences in conjunction with published sequences were subjected to multiple phylogenetic analyses. Furthermore the nuclear dataset was also subjected to molecular dating analysis to ascertain the divergence between H. anamallensis and related genera. Results and Conclusion Results showed that H. anamallensis lineage was indeed sister to Hemidactylus group but was separated from the rest of the Hemidactylus by a long branch. The divergence estimates supported a scenario wherein H. anamallensis dispersed across a marine barrier to the drifting peninsular Indian plate in the late Cretaceous whereas Hemidactylus arrived on the peninsular India after the Indian plate collided with the Eurasian plate. Based on these molecular evidence and biogeographical scenario we suggest that the genus Dravidogecko should be resurrected.